The longitudinal relationship between sleep length and psychotic-like experiences in adolescents: short communication - Zhou, Rui; Foo, Jerome Clifford; Yamaguchi, Satoshi; Nishida, Asuka; Ogawa, Sayoko; Usami, Satoshi; Togo, Fumiharu; Sasaki, Tsukasa (Psychiatry research, 2022)
The longitudinal relationship between psychotic-like experiences (PLEs) and short habitual sleep in adolescents remains to be investigated. We examined the effect of habitual sleep length (time-in-bed: TIB) on the risk of subsequent year PLEs and vice versa, in grade 7-12 students (ages: 12-18, n = 1,685) followed over 6 years. Yearly longitudinal data were analyzed using cross-lagged panel models. Shorter weekday TIB was associated with a higher risk of subsequent year PLEs; PLEs did not affect subsequent year TIB. Compared to a TIB of 8-9 h, 5-6 h increased PLEs likelihood 1.8 times; <5 h increased this 6-fold.